Diversity of plankton in the waters of sanghyang kenit Rajamandala cave, Indonesia - Rahmat Taufiq Mustahiq Akbar; Sella Nur Devi; Isma Dwi Kurniawan; Risda Arba Ulfa; Adisty Virakawugi Darniwa (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Sanghyang Kenit Cave is a cave that has an aquatic environment and a potential habitat for plankton. Plankton can be a bioindicator of water because of its sensitivity to the environment. The purpose of this study was to determine the diversity, interrelationship factors, and linkages of plankton with the environment in the waters of Sanghyang Kenit Rajamandala Cave, West Bandung. This research was conducted from August 2021 to September 2022. The study employed a purposive sampling method, identifying three sampling zones (The Light, Twilight, and Dark zones) during morning, afternoon, and evening periods. Sampling was done by taking a sample of 10 liters and then filtering using plankton net. The Physico-chemical parameters measured included water temperature, light intensity, pH, DO, salinity, nitrate, and phosphate. Based on the results of data analysis found 4 classes with 12 plankton morphospecies. Diversity index values in the Light zone (1.10), Twilight zone (1.08), and dark zone (1.08). Abundance index value in the light zone is 2.537 cells/l, the twilight zone is 501 cells/l, and the dark zone is 29 cells/l. Diversity and plankton in the waters of Sanghyang Kenit Cave have a very strong correlation with water temperature, light intensity, and pH of water. This can be the basis for the development of further research on the management and monitoring of caves that are used as tourist attractions.KeywordsDiversityPlanktonSanghyang Kenit CaveEnvironment